Combination of mathematical literacy with ethnomathematics: How to perspective sundanese culture - Uba Umbara; Sufyani Prabawanto; Mohamad Gilar Jatisunda (IKIP Siliwangi and I-MES, 2023)
Mathematical literacy and ethnomathematics are the two main approaches to understanding mathematics in everyday life. Research on the two aspects should be conducted in an integrated manner. It is expected to be a reference for the development of urban mathematics education based on the social requirements of mathematics and individuals' mathematical competence in a cultural group. The primary goal of this research is to describe the Sundanese people's mathematical literacy through an ethnomathematical perspective. The research is focused on living equipment systems and technology, which is one of the elements of the seven universal culture elements. The study employed phenomenographic and ethnomethodological approaches with a realist ethnographic design. Participant observations and interviews were chosen as data collection techniques, while content analysis, triangulation, and identification of patterns were chosen as data analysis techniques. Ethnomathematics in living equipment systems and technology consists of counting, measuring, explaining, discovering, designing, and explaining activities. The results show that the ethnomathematics of the Sundanese community are relevant to the aspects of mathematical literacy consisting of content, context, and mathematical processes. The study's results emphasize that mathematical literacy and ethnomathematics cannot be separated from daily life.